2015
DOI: 10.3389/fnana.2015.00090
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of vasotocin- and vasoactive intestinal peptide-like immunoreactivity in the brain of blue tit (Cyanistes coeruleus)

Abstract: Blue tits (Cyanistes coeruleus) are songbirds, used as model animals in numerous studies covering a wide field of research. Nevertheless, the distribution of neuropeptides in the brain of this avian species remains largely unknown. Here we present some of the first results on distribution of Vasotocine (AVT) and Vasoactive intestinal peptide (VIP) in the brain of males and females of this songbird species, using immunohistochemistry mapping. The bulk of AVT-like cells are found in the hypothalamic supraoptic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 133 publications
0
10
0
Order By: Relevance
“…Therefore, this served as our guide for selection of additional hypothalamic brain regions, which included paraventricular (PVN) and ventromedial hypothalamic nuclei (VMN; Figure 1C,D) as well as the lateral (LH) and tuberal hypothalamic regions (TU; Figure 1C,D). Brain punches of these regions were based on Stokes neuroanatomical atlas 53 as well as brain regions illustrated in Reference 63. Figure 1A,B illustrate punches that were included in Next Generation Sequencing (NGS) of the POA.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this served as our guide for selection of additional hypothalamic brain regions, which included paraventricular (PVN) and ventromedial hypothalamic nuclei (VMN; Figure 1C,D) as well as the lateral (LH) and tuberal hypothalamic regions (TU; Figure 1C,D). Brain punches of these regions were based on Stokes neuroanatomical atlas 53 as well as brain regions illustrated in Reference 63. Figure 1A,B illustrate punches that were included in Next Generation Sequencing (NGS) of the POA.…”
Section: Methodsmentioning
confidence: 99%
“…Schematic drawings of the transverse sections of the brain of T. guttata were prepared using CorelDraw 12 software (Ottawa, Canada). The terminology and identification of the areas of the brain and cell nuclei were adopted from previous studies on birds (Avian nomenclature forum: Reiner et al, ; Stereotaxic atlas of the brain of canary, Serinus canaria : Stokes et al, ; chicken: Kuenzel and Masson, ; Puelles et al, ; terminology outlined by Montagnese et al, for the brain of the blue tit, Cyanistes coeruleus ; brain atlas of crow: Izawa and Watanabe, ; and the digital: Karten et al, , and stereotaxic: Nixdorf‐Bergweiler and Bischof, , atlas of the zebra finch brain). The nomenclature of the septal subdivisions was adopted from the chemoarchitectonic subdivisions of the songbird septum (Goodson et al, ) and nucleus accumbens as described by Alger et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The Avian Brain Nomenclature Consortium (Reiner, Perkel, Mello, & Jarvis, ) proposed several arcopallial subdivisions, consisting of anterior, intermediate, dorsal, and medial parts, as well as the posterior pallial amygdala (PoA), subpallial amygdaloid area (SpA), and nucleus taenia of the amygdala (TnA). Furthermore, some studies provide evidence that discrete arcopallial areas can be identified through immunohistochemical staining for select markers like neuropeptides (e.g., Montagnese, Szekely, Csillag, & Zachar, ), or differential regional binding of ligands for neurotransmitter receptors (Herold et al, ). In some cases, discrete arcopallial nuclei that participate in specific circuits and/or functions are readily identifiable.…”
Section: Introductionmentioning
confidence: 99%